2018
DOI: 10.1016/j.jbankfin.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Competition or manipulation? An empirical evidence of determinants of the earnings persistence of the U.S. banks

Abstract: We examine the impact of competition on bank earnings persistence by exploiting a natural experiment following interstate banking deregulation that increased bank competition. We find that bank earnings adjustment speed increases after the state where the bank locates implements the deregulation. This relationship is weakened, however, with the increase of banks' abilities to sustain earnings, as reflected in size, diversification, managerial efficiency and safety. We further find that compeititon directly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…The ROE provides a direct assessment of the financial return on a shareholder's investment (Lee and Kim, 2013) and the ROA shows the bank's ability to generate income using assets (Ongore and Kusa, 2013). ROE is the ratio between net income and equity (Athanasoglou et al, 2008;Firth et al, 2016;Tan, 2016;Bikker and Vervliet, 2017) and ROA represents the quotient between the net income and the total assets (Liu et al, 2014;Saghi-Zedek and Tarazi, 2014;Chronopoulos et al, 2015;Hung et al, 2018). Dietrich and Wanzenried (2011) and Meles et al (2016) use as the denominator the total average assets and total average equity, respectively.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…The ROE provides a direct assessment of the financial return on a shareholder's investment (Lee and Kim, 2013) and the ROA shows the bank's ability to generate income using assets (Ongore and Kusa, 2013). ROE is the ratio between net income and equity (Athanasoglou et al, 2008;Firth et al, 2016;Tan, 2016;Bikker and Vervliet, 2017) and ROA represents the quotient between the net income and the total assets (Liu et al, 2014;Saghi-Zedek and Tarazi, 2014;Chronopoulos et al, 2015;Hung et al, 2018). Dietrich and Wanzenried (2011) and Meles et al (2016) use as the denominator the total average assets and total average equity, respectively.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…However, the main components of earnings quality are accountability and transparency, which predict the future earnings persistence of the firm to the investors and stakeholders. This information is essential and relevant for the investors and stakeholders to make the specific decision related to the future performance of the firm (Hung et al, 2018). As the stability and the persistence of reported earnings are the fundamentals of earnings quality.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the number of prior studies that explored the EM-EP relationship is still limited. Hung and Jiang [8] conducted their study with a sample of 15,546 U.S commercial banks from 1986 to 2013. From the economic competition theory perspective, they suggested a positive relationship between EM and persistence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…EPs are defined as the durability and repetition of earnings and indicate the extent to which present profits may be sustained in the future [4][5][6]. Numerous prior research studies have established a relationship between the quality of earnings reported in financial statements and EP [6][7][8][9]. Earnings quality may be worse, and earnings may be unsustainable, as observed by lower EPs [10].…”
Section: Introductionmentioning
confidence: 99%